The Introductive Baka/Bāki in Rural Palestinian Arabic - Shachmon, Ori (Journal of Semitic studies, 2021)
The article explores the structure and use of the existential verb baka in Rural Palestinian Arabic for the introduction of orientation sections and fragments in narrative discourse. In clause-initial position the existential verb presents a non-inflecting form, either the 3MSG perfect baka or the MSG active participle bāki. We argue that the noninflectability of baka and bāki is indicative of their syntactic detached-ness from the following unit and is explained by their discourse-disjunctive function. We show that the existential baka/bāki serves to introduce both narrative-initial and narrative-embedded orientation. It may initiate utterances containing simple nominals or whole clauses. The distribution of the specific patterns is determined, inter alia, by the genre of the narrative told. Finally, we propose that the preference of the participle bāki over baka in folktales and in less committed instances of personal narratives may be related to the evidential function of the active participle in the dialects under examination.